PELATIHAN TUNE UP SEPEDA MOTOR SEBAGAI PENINGKATAN KOMPETENSI PRAKTIKAL SISWA PADA WILAYAH ULAPAN (UBUD, TEGALALANG, DAN PAYANGAN) UNTUK MENDUKUNG KAWASAN STRATEGIS PARIWISATA NASIONAL (KSPN) (JPMPPI (Jurnal Pengabdian Masyarakat), 2022)
This Community Service Activity Motorcycle Tune Up Training aims to improve the practical competence of students at SMKN 1 Tegalalang so that they can tune up motorcycles effectively, efficiently and safely, including: checking, maintaining, repairing and adjusting motorcycle parts/systems according to the Tune Up procedure, and has an outcome in the form of increasing scientific competence, especially regarding engine parts, electrical parts, and motorcycle chassis parts. The method of this activity is to conduct training for students in grades 10, 11, and 12 of the Automotive Department at SMKN 1 Tegalalang. Training in the form of providing materials and practice in the field with a percentage of 30% for material and 70% for practice. The basis of doing Tune Up on a motorcycle is that every motorcycle that is operated, will eventually experience a situation where the parts of the motorcycle (engine, transmission, frame, etc.) experience fatigue and wear and tear, thereby reducing its performance, including: engine power decline, slow acceleration, wasteful fuel and the possibility of continuing/spreading damage to other component damage and to support the national tourism strategic area (KSPN) especially the ULAPAN area (Ubud, Tegalalang and Payangan) in order to increase the economic factors of the region. This activity was carried out in collaboration with the Bali Land Transportation Polytechnic with SMKN 1 Tegalalang. The result of this Community Service activity is an increase in the practical competence of SMKN 1 Tegalalang students so that later they can be used as provisions to set up a workshop business (MSME level) or work